2018
DOI: 10.1111/1475-6773.12833
|View full text |Cite
|
Sign up to set email alerts
|

Medicare Payment Penalties and Safety Net Hospital Profitability: Minimal Impact on These Vulnerable Hospitals

Abstract: Safety net hospitals appear to rely on nonpatient care revenues to offset higher penalties for the years studied. While reassuring, these funding streams are volatile and may not be able to compensate for cumulative losses over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 14 publications
0
38
1
Order By: Relevance
“…The important findings of this research are that there is evidence that there has been a decline in readmissions across the board, and in some cases with more substantial changes for vulnerable populations. Although previous studies using pre-HRRP data raised concerns that the policy might disproportionally penalize vulnerable hospitals and patients [2–4], post-HRRP studies found that the HRRP penalty did not significantly affect the financial performance of vulnerable hospitals in particular (e.g., safety-net hospitals [8]). Together with our findings, this suggests that HRRP appears to be creating the right incentives for reducing readmissions not only overall but also for vulnerable populations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The important findings of this research are that there is evidence that there has been a decline in readmissions across the board, and in some cases with more substantial changes for vulnerable populations. Although previous studies using pre-HRRP data raised concerns that the policy might disproportionally penalize vulnerable hospitals and patients [2–4], post-HRRP studies found that the HRRP penalty did not significantly affect the financial performance of vulnerable hospitals in particular (e.g., safety-net hospitals [8]). Together with our findings, this suggests that HRRP appears to be creating the right incentives for reducing readmissions not only overall but also for vulnerable populations.…”
Section: Resultsmentioning
confidence: 99%
“…These changes could affect readmission rates. Because Medicaid expansion took effect in 2014, our paper and other studies on HRRP [7, 8, 14, 28, 29] generally chose the sample period up to 2014 to avoid this potential problem. However, it is possible that hospitals, patients and insurance companies had already made changes during or before 2014.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With a poor performance rating also impacting patient confidence, hospitals are searching for affordable ways to reduce HAIs. 14 17 …”
Section: Introductionmentioning
confidence: 99%